Using blockchain technology in Intelligent Control Systems - البكور علاء (Latakia University Journal -Engineering Sciences Series, 2024)
Data security is especially important in automation systems that require the exchange of data over large distances through both telecommunications and telecommunications, which in turn is a fertile environment for piracy, not far from the attack on the Manouchehr nuclear reactor in Iran. The use of Blockchain technology may increase the security of the data exchanged because it is difficult to intercept its messages through its encryption system, and it also ensures the integrity of this data. In this research, a blockchain algorithm was proposed that works on the same microcontroller and uses the RS322 serial connection and was tested by using the Atmega2560 controller (an 8-bit processor with 8 KB SRAM memory) for a smart home system that measures temperature and humidity, as well as senses the presence of gas and measures the intensity of lighting in order to control the equipment of this house, the results proved that it is not possible to Use this technique on microcontrollers.